A simple controller for the prediction of three-dimensional gait - Fluit, R.; van der Krogt, M.M.; van der Kooij, H.; Verdonschot, N.; Koopman, H.F.J.M. (Journal of biomechanics, 2012)
The objective of this study is to investigate the potential of forward dynamic modeling in predicting the functional outcome of complicated orthopedic procedures involving relocation or removal of muscles or correction osteotomies in the lower extremities. For this purpose, we developed a torque actuated forward dynamics based three-dimensional model of gait, that extends the previous reported work of Van der Kooij et al. (2003). The mechanical properties are scaled to the subject and lateral stability is provided by an ‘offset plus proportional’ controller (Hof, 2008). Kinematic constraints are formulated based on three independent gait descriptors and implemented in an optimization algorithm. The computational effort is small (1min per gait cycle on a 1GHz processor) and the control scheme generates symmetric and cyclic gait based on the desired gait descriptors. An interface with the inverse dynamics based AnyBody Modeling System, a musculoskeletal modeling tool, provides insight in muscle activities. The proposed control scheme is robust against mediolateral perturbations. The predictive capacity of the model is evaluated by simulating pathological gait by means of weakening the hip abductors, and the model is able to predict some of the trends of compensatory strategies in such a perturbed mechanical system.